2013
DOI: 10.1371/journal.pone.0079645
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Differentiation between Livestock-Associated and Livestock-Independent Staphylococcus aureus CC398 Clades

Abstract: Staphylococcus aureus clonal complex 398 (CC398) isolates cluster into two distinct phylogenetic clades based on single-nucleotide polymorphisms (SNPs) revealing a basal human clade and a more derived livestock clade. The scn and tet(M) genes are strongly associated with the human and the livestock clade, respectively, due to loss and acquisition of mobile genetic elements. We present canonical single-nucleotide polymorphism (canSNP) assays that differentiate the two major host-associated S. aureus CC398 clade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 29 publications
5
84
0
5
Order By: Relevance
“…Other STs described in pigs are ST541, ST1965, ST1966, ST1967, and ST1968 [16,35,36]. However, it has been shown that there is a specific subgroup of human ST398 strains, different from LA-MRSA ST398 [37], that can be readily differentiated by SNP detection and the presence or absence of scn and tet(M) [38]. Research in the Netherlands revealed that all the CC398 strains there typically are LA-MRSA [39].…”
Section: Cc398mentioning
confidence: 99%
“…Other STs described in pigs are ST541, ST1965, ST1966, ST1967, and ST1968 [16,35,36]. However, it has been shown that there is a specific subgroup of human ST398 strains, different from LA-MRSA ST398 [37], that can be readily differentiated by SNP detection and the presence or absence of scn and tet(M) [38]. Research in the Netherlands revealed that all the CC398 strains there typically are LA-MRSA [39].…”
Section: Cc398mentioning
confidence: 99%
“…Jego obecność stwierdza się prawie u wszystkich profagów φ3. Gen chp kodujący białko hamujące chemotaksję (CHIPS, chemotaxis inhibitory protein) występuje u około 50% profagów (47). Ponadto około 75% profagów zawiera gen sak odpowiedzialny za wytwarzanie stafylokinazy oraz u połowy fagów wykrywa się geny odpowiedzialne za wytwarzanie enterotoksyn typu A oraz typu P, o wła-ściwościach superantygenów (25).…”
Section: Struktura Genomu Staphylococcus Aureusunclassified
“…Szczepy uznane za typowo "ludzkie" określono jako CC398-I/II-GOI, natomiast związane ze zwierzętami jako CC398-IIa (47). Obie linie można odróżnić na podstawie wyników analizy polimorfizmu pojedynczego nukleotydu.…”
Section: Struktura Genomu Staphylococcus Aureusunclassified
See 2 more Smart Citations